Possible Role of Human Herpesvirus 6 as a Trigger of Autoimmune Disease. (24th October 2013) - Broccolo, Francesco; Fusetti, Lisa; Ceccherini-Nelli, Luca
Abstract : Human herpesvirus 6 (HHV-6) infection is common and has a worldwide distribution. Recently, HHV-6A and HHV-6B have been reclassified into two distinct species based on different biological features (genetic, antigenic, and cell tropism) and disease associations. A role for HHV-6A/B has been proposed in several autoimmune disorders (AD), including multiple sclerosis (MS), autoimmune connective tissue diseases, and Hashimoto's thyroiditis. The focus of this review is to discuss the above-mentioned AD associated with HHV-6 and the mechanisms proposed for HHV-6A/B-induced autoimmunity. HHV-6A/B could trigger autoimmunity by exposing high amounts of normally sequestered cell antigens, through lysis of infected cells. Another potential trigger is represented by molecular mimicry, with the synthesis of viral proteins that resemble cellular molecules, as a mechanism of immune escape. The virus could also induce aberrant expression of histocompatibility molecules thereby promoting the presentation of autoantigens. CD46-HHV-6A/B interaction is a new attractive mechanism proposed: HHV-6A/B (especially HHV-6A) could participate in neuroinflammation in the context of MS by promoting inflammatory processes through CD46 binding. Although HHV-6A/B has the ability to trigger all the above-mentioned mechanisms, more studies are required to fully elucidate the possible role of HHV-6A/B as a trigger of AD.